Design of a Patient Wrist Rehabilitation Device with Servo Motor Drive - Lukman Yassir Amali; I Made Londen Batan (JMES: The International Journal of Mechanical Engineering and Sciences, 2020)
Stroke represents a condition that occurs when the blood supply to the brain is interrupted or reduced due to a blockage (ischemic stroke) or rupture of a blood vessel (hemorrhagic stroke). A person who suffers a stroke will have a brain disorder that causes him/her unable to carry out activities like other healthy people. In general, stroke sufferers have paralysis in several parts of the body, like the hands, feet, and even the face. With technological developments in this era, stroke can be healed in various ways that have been developed by health experts. Healing can be referred to the treatment result for blocked or damaged blood vessels. However, the sufferer’s paralysis cannot return to the normal condition immediately, so it requires therapy or exercises to stimulate the muscles in the hands, feet, or face. This study focuses on developing a therapeutic device on the wrist that has a swivel joint. To design the wrist rehabilitation device with servo motor drive, some researches about existing products need to be reviewed. From that, a list of requirements is compiled, which is used for designing the concept of a wrist rehabilitation device. It is expected that an automatic wrist rehabilitation device can help post-stroke patients undergo the rehabilitation process.